Kombinasi Aromaterapi Lavender dan Brain Gym Efektif terhadap Penurunan Tingkat Stres pada Mahasiswa Kebidanan Semester VI - Dian Puspita Reni; Rezki Puspitaningsih; Fara Imelda Theresia Patty; Ratna Wati (POLTEKKES KEMENKES MANADO, 2022)
Background: Stress is the body's mental and physiological response to a physical. Students in the final semester have a heavier load and task. Students are prone to experiencing stress during the educational process. Handling stress can be solved with relaxation combined between lavender therapy and brain gym. The purpose was to determine the effectiveness of combination between lavender therapy and brain gym on decreasing stress level. Method: Quasi-experimental research with time series design. Sample was 24 people. Technique sampling used purposive sampling with inclusion and exclusion criteria. Lavender aromatherapy and brain gym are independent variables, student stress level is dependent variable. The daily data analysis technique of pretest and posttest stress levels uses Marginal Homogeneity and differences in stress levels using Friedman's test with post-hoc Wilcoxon. Result: Marginal Homogeneity test for stress levels on 1st day to 7th day of pretest and posttest obtained a significance value ρ <0.05 and Friedman's test with Post-hoc Wilcoxon 0,000 (ρ < 0.001). Conclusion: The combination of lavender aromatherapy and brain gym is effectively decreasing stress level on Semester VI of Midwifery Student and there is a difference in stress levels between pretest and posttest on 1st day to 7th day.